Analysis of Factors Associated with The Incidence of Stunting among Toddlers in The Working Area of Baron Health Center, Nganjuk District, Indonesia - Marminingsih; Yenny Puspitasari; Rahmania Ambarika (Ficco Scientific Corner, 2025)
Background: Cases of stunting in children under five are still high. The prevalence of stunting in toddlers in Nganjuk Regency reached 17.1% (13,821 children aged 0-59 months). This study aims to analyze the factors associated with the incidence of stunting in toddlers aged 0-59 months in the working area of the Baron Health Center, Nganjuk Regency. Methods: This research is a quantitative study using a Cross Sectional study design. Total population 3,028 toddlers, with a sample of 379 children. Analysis using the Chi Square test. Results: The results of statistical tests of pregnant women who experience Chronic Energy Deficiency (CED), it can be concluded that there is a relationship between the status of pregnant women Chronic Energy Deficiency (CED) and the incidence of stunting in toddlers with a significance value is < 0.01. Women with anemia who are pregnant A significant correlation has been found between toddler stunting incidence and anemic status. is <0.01 and pregnant women who suffer from comorbidities there is a relationship between the history of comorbidities in pregnant women with the incidence of stunting in toddlers with a significance value is < 0.01. Conclusions: The incidence of stunting in toddlers can be caused by various factors. This study proves that pregnant women experiencing Chronic Energy Deficiency (CED) anemic pregnant women, and a history of comorbidities are significantly associated with the incidence of stunting in toddlers (sig < 0.01 < 0.05).